The Role of the Marine and Fishery Sector on Regional Original Income (PAD) Fakfak Regency - Agustina Waromi; Raklan Gultom; Pitrolena Sahetapy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Regional Original Income during the period of four years there was an increase and decrease in revenue sources from the marine and fisheries sector. This is not because the role and performance of the marine and fisheries sector has decreased, but for the last 2 (two) years there has been a separation between Fakfak Regency and Kaimana District, so that in mid-2004 the collection of retribution from Fakfak Regency was officially stopped. The research method is qualitative. The results of the study show that the results of the analysis of the increase in Regional Original Revenue in the Maritime and Fisheries Service sector of Fakfak Regency originating from certain licensing revenue sources from Fisheries Business Permits and Certificates of Origin from 2015 - 2017 amounted to 43%, from 2016 - 2018 amounted to 43%. 36%, from 2017 – 2019 receipts of Retribution for Fisheries Business Permits (SIUP), and Certificates of Origin (SKA) decreased by 3.24%, from the results of this analysis it shows an increase in Regional Original Income from the Marine and Fisheries sector in 2016 - 2019 always changing or fluctuating and the results are increasing seen in 2015 – 2017 an increase of 43%. The implementation of Regional Original Revenue Sources at the Marine and Fisheries Service of Fakfak Regency, through Business Permits (SIUP) and Certificates of Origin (SKA) from 2015 to 2016 has increased by Rp.664,170,273, - or 43 percent (%) but in 2018 to 2019 it decreased by Rp. 320,115,350, - or 3.24 percent.